Marketing Channel Analysis and Driving Factors For Sugarcane Farmers' Choice of Marketing Channels of Cinta Manis Sugar Factory Partners: Analisis Saluran Pemasaran Serta Faktor-Faktor Pendorong Pemilihan Saluran Pemasaran Gula Pasir Petani Tebu Mitra Pabrik Gula Cinta Manis - Karimah, Aqila Rizky; Rosana, Elly (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
Determining an appropriate marketing channel for granulated sugar is a significant step for sugarcane farmers because each marketing channel offers different profit margins for them. The objectives of this study are: (1) Analyzing the marketing channels and marketing margins of sugarcane farmers' sugar in the vicinity of the Cinta Manis Sugar Factory. (2) Analyzing the driving factors for farmers in selecting marketing channels for sugarcane farmers partnering with the Cinta Manis Sugar Factory. (3) Analyzing the income of sugarcane farmers from the sale of sugar through profit-sharing with the Cinta Manis Sugar Factory. This research was conducted in the vicinity of the Cinta Manis Sugar Factory in Ogan Ilir Regency from December 2023 to January 2024. The research location was purposively chosen. The research method employed was the Survey Method. The sampling method utilized Purposive Sampling with specific criteria, selecting 15 farmers out of a total of 40 sugarcane farmers. The data used comprised both primary and secondary data. Data processing for each objective employed descriptive analysis, Likert scale analysis, and formulas. The research findings revealed that sugarcane farmers chose 2 types of marketing channels to market their sugar. The driving factors influencing farmers' decisions in selecting a marketing channel, with the greatest impact, were price, social trust, sugar quantity, and sales distance. The average income of sugaecane farmers from selling sugars is RpRp92.581.564. per year. Sugarcane farmers' income from sugar sales ranged from Rp15,153,501 to Rp21,830,424 per hectare of land per year. Keywords: marketing channels, sugarcane farmers, sugar